2014
DOI: 10.1177/1079063214544329
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Familiarity With Sexual Abusers to Subsequent Developmental Adaptation in Youths Who Have Sexually Offended

Abstract: The present study explored the effects of child sexual abuse (CSA) on the adaptation of male juveniles who subsequently sexually offended (JSOs; n = 178; age, M = 16.05 years, SD = 0.27, range = 12-22). It examined multiple levels of interpersonal closeness between the perpetrators of sexual abuse and their JSO victims. JSOs who were sexually abused by older children or adults who cohabitated with them for at least 3 months reported higher levels of emotional dysregulation, callousness/manipulativeness, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…The current finding that sexual abuse emerged as a significant predictor of normophilic sexualization is consistent with previous literature linking childhood sexual abuse to the development of excessive normative sexual thoughts and behaviors in juvenile sexual and nonsexual offender samples (Berman & Knight, 2015;Grabell & Knight, 2009;Knight, 2004;Miner et al, 2010). In a meta-analysis of male adolescent samples in the United States and Canada, Homma et al (2012) found that males with a history of sexual abuse were significantly more likely to have engaged in a variety of risky sexual behaviors, including behaviors related to hypersexuality, such as having sex with multiple partners.…”
Section: Normophilic Excessive Sexualizationsupporting
confidence: 91%
See 4 more Smart Citations
“…The current finding that sexual abuse emerged as a significant predictor of normophilic sexualization is consistent with previous literature linking childhood sexual abuse to the development of excessive normative sexual thoughts and behaviors in juvenile sexual and nonsexual offender samples (Berman & Knight, 2015;Grabell & Knight, 2009;Knight, 2004;Miner et al, 2010). In a meta-analysis of male adolescent samples in the United States and Canada, Homma et al (2012) found that males with a history of sexual abuse were significantly more likely to have engaged in a variety of risky sexual behaviors, including behaviors related to hypersexuality, such as having sex with multiple partners.…”
Section: Normophilic Excessive Sexualizationsupporting
confidence: 91%
“…Samples of adults have comparably high testretest reliability and internal consistency, and both juveniles and adults have shown considerable agreement in responding across domains (Knight, 2004;Knight et al, 1994). The MASA has been validated across samples of adults with sexual and nonsexual offenses, juveniles with sexual and nonsexual offenses, college students, and community samples (Berman & Knight, 2015;Daversa & Knight, 2007;Grabell & Knight, 2009;Knight, 2004;Knight & Cerce, 1999;Knight et al, 1994;Knight & Sims-Knight, 2003Zakireh et al, 2008). The focus for the present study was on the sections of the MASA that assess developmental abuse histories, as well as the scales used to assess problematic sexual thoughts and behaviors.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations